2008
DOI: 10.1118/1.2896076
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of P‐32 ophthalmic applicator: Monte Carlo simulations for design and dosimetry

Abstract: Postoperative beta-irradiation after pterygium excision has been considered a valuable therapeutic procedure to reduce the recurrence rate. Recently, it was reported that beta-irradiation also substantially reduced the risk of surgical failure after glaucoma surgery. Pure beta-irradiation using a 90Sr/Y applicator has been almost exclusively used for this purpose. As an alternative to 90Sr/Y beta-irradiation, we propose treatment with betas of a 32P source. While 32P has a lower maximum energy (1.71 MeV) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In Ref. 11, we demonstrated that an appropriately designed 32 P applicator could deliver doses to the target lesion similarly to or better than 90 Sr=Y and the HANARO reactor (30 MW) could generate a sufficient neutron flux that produced 32 P activities required to deliver the therapeutic doses.…”
Section: Iia Source and Applicatormentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. 11, we demonstrated that an appropriately designed 32 P applicator could deliver doses to the target lesion similarly to or better than 90 Sr=Y and the HANARO reactor (30 MW) could generate a sufficient neutron flux that produced 32 P activities required to deliver the therapeutic doses.…”
Section: Iia Source and Applicatormentioning
confidence: 99%
“…1 of Ref. 11. We assumed that the source activity was uniformly distributed in the entire volume of absorbent disk.…”
Section: Iie Monte Carlo Simulationsmentioning
confidence: 99%
See 3 more Smart Citations